Chemistry and Bioactivity of Haplopappus Remyanus ("Bailahuen"), a Chilean Medicinal Plant - Torres-Gaona, M (2011)
Chromatography on the resinous extract of aerial parts of Haplopappus remyanus led to the isolation of 18-acetoxy-labda-7,13E-dien-15-oic acid along with the monoterpene derivatives 9-hydroxy-?-terpineol, 9-benzoyloxy-?-terpineol,7-hydroxy-9-benzoyloxy-?-terpineol and 9-benzoyloxy-(1-formyl)-?-terpineol. Structures for the new compounds are proposed on spectroscopic evidence. The presence of quercetin and five other known flavonoids identified in this study could account for the reported high antioxidant activity and the moderate topic anti-inflammatory effect on induced ear oedema. MTT assay with CCRF-CEM tumor cells showed 50% of the cytotoxic activity displayed by doxorubicin under the same conditions. Quantitative differences in chemical composition were detected in comparison with previous studies of the species that could be attributed to environmental factors. © 2011 Sociedade Brasileira de Química.